Distinct gene alterations with a high percentage of myeloperoxidase-positive leukemic blasts in de novo acute myeloid leukemia. (February 2018) - Kamijo, Rena; Itonaga, Hidehiro; Kihara, Rika; Nagata, Yasunobu; Hata, Tomoko; Asou, Norio; Ohtake, Shigeki; Shiraishi, Yuichi; Chiba, Kenichi; Tanaka, Hiroko; Miyano, Satoru; Ogawa, Seishi; et al.
Highlights: Relationship between MPO-positivity and gene mutations was analyzed in de novo AML. MPO-positivity of AML blasts correlated with the distinct gene mutation patterns. CEBPA and IDH1/2 & TET2 & WT1 mutations were more frequently detected in MPO-high group. DNMT3A and TP53 mutations were more frequently detected in MPO-low group. Abstract: The myeloperoxidase (MPO)-positivity of blasts in bone marrow smears is an important marker for not only the diagnosis, but also the prognosis of acute myeloid leukemia (AML). To investigate the relationship between genetic alterations and MPO-positivity, we performed targeted sequencing for 51 genes and 10 chimeric gene transcripts in 164 newly diagnosed de novo AML patients; 107 and 57 patients were classified as AML with >50% MPO-positive blasts (MPO-high group) and ≤50% MPO-positive blasts, (MPO-low group), respectively. The univariate analysis revealed that RUNX1-RUNX1T1 ( P <  0.001), the KIT mutation ( P  <  0.001), and CEBPA double mutation ( P  = 0.001) were more likely to be found in the MPO-high group, while the DNMT3A mutation ( P  = 0.001), FLT3 tyrosine kinase domain mutation ( P  = 0.004), and TP53 mutation ( P  = 0.020) were more likely to be present in the MPO-low group. Mutations in genes related to DNA hypermethylation signatures ( IDH1, IDH2, TET2, and WT1 genes) were more frequent in the MPO-high group ( P  = 0.001) when patients with fusion genes of core-binding factors were excluded from the analysis. Our results suggest that MPO-positivity of blasts was related with the distinct gene mutation patterns among de novo AML patients.